Уравнение с дескрименантом (х-9)(2-х)=0

0 голосов
67 просмотров

Уравнение с дескрименантом (х-9)(2-х)=0


Алгебра (26 баллов) | 67 просмотров
Дан 1 ответ
0 голосов

(x-9)(2-x)=0

2x-x^2-18+9x=0

-x^2+11x-18=0 | *(-1)

x^2-11x+18=0

a=1; b=-11; c=18.

D=b^2-4ac=(-11)^2-4*1*18=121-72=49

X1=(-b+ \sqrt{D} )/(2a)=(-(-11)+ \sqrt{49})/(2*1)

X1=(11+7)/2=18/2=9

X2=(-b- \sqrt{D})/(2a)=(-(-11)- \sqrt{49})/(2*1)

X2=(11-7)/2=4/2=2

X1=9; X2=2

0

или

0

2x-1=0

0

2x=1

0

x2=0,5

0

Jndtn

0

X1=0

0

X2=0,5

0

ты сам(а) понимаешь что ты пишешь?

0

да

0

ладно не надо лучше сам решу